2022
DOI: 10.3389/fnhum.2022.876083
|View full text |Cite
|
Sign up to set email alerts
|

Transcranial direct current stimulation over the posterior parietal cortex improves visuomotor performance and proprioception in the lower extremities

Abstract: The purpose of this study was to examine whether anodal transcranial direct current stimulation (a-tDCS) over the posterior parietal cortex (PPC) could affect visuomotor performance and proprioception in the lower extremities. We evaluated visuomotor performance in 15 healthy volunteers using a visuomotor control task by plantar dorsiflexion of the ankle joint, and calculated the absolute difference between the target and measured angle. In addition, we evaluated proprioception using a joint position matching … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(3 citation statements)
references
References 55 publications
0
3
0
Order By: Relevance
“…It is also possible that the neuronal ring rate was increased but did not signi cantly affect the postural control response. Anodal tDCS to the PPC did not signi cantly increase the neural ring rate, suggesting that there was no signi cant change in absolute error in the lower limb joint position matching task [35]. These considerations are also applicable to the tRNS results.…”
Section: Discussionmentioning
confidence: 78%
See 1 more Smart Citation
“…It is also possible that the neuronal ring rate was increased but did not signi cantly affect the postural control response. Anodal tDCS to the PPC did not signi cantly increase the neural ring rate, suggesting that there was no signi cant change in absolute error in the lower limb joint position matching task [35]. These considerations are also applicable to the tRNS results.…”
Section: Discussionmentioning
confidence: 78%
“…It has been reported that the tDCS slightly increases the neural excitability of the brain regions receiving anodal stimulation [32], and the tRNS synchronizes the cellular ring of large populations by propagating from a single cell to neuronal cells at the population level through stochastic resonance mechanisms [33,34]. Previous research has shown that anodal tDCS and tRNS to the PPC can alter body performance such as tactile perception and joint position matching [13,35]. Although these tES techniques reportedly increased the excitability of the PPC region by adapting P4, this study did not induce changes in body control responses.…”
Section: Discussionmentioning
confidence: 99%
“…They used visual biofeedback along with exercise training in patients with knee arthroscopy and suggested that information received through visual feedback could act as a sensory alternative to compensate for the proprioception of the injured limb in patients (39). Regarding the effect of tDCS, on the other hand, the previous studies have also demonstrated that it could have a positive role in the improvement of absolute error of proprioception in healthy young people (40)(41)(42) and patients with tendinitis (43). Stagg et al indicated that applying tDCS over left dorsolateral prefrontal cortex (DLPFC) caused increased activity of the sensorimotor cortex and decreased activity of the thalamus.…”
Section: Discussionmentioning
confidence: 99%